An Introductory Study of Commentaries of Ṣaḥiḥ Bukhari written by the Scholars of Khyber Pakhtunkhwa - Khan, Muhammad Ismail (Journal of Islamic and Religious Studies, 2018)
Shah Waliullah pioneered the promulgation and publication of Ḥadtih in the Subcontinent. His immediate students and avid readers owned this sacred responsibility and brought forth this beacon of Ḥadtih in Khyber Pakhtunkhwa, posthumously. In the said region, not only a meticulous research has been conducted on assorted genres of Ḥadtih but also a profound work has been executed on its treatise. Especially, “The Ṣaḥiḥ Bukhari” has remained the focus for research and analysis. Besides, in madaris of Khyber Pakhtunkhwa, different sermons and oral disquisitions of the noteworthy religious scholars and Ḥadtih experts (specifically “Ṣaḥiḥ Bukhari”) have been recorded and published in several books and booklets. In this respect, the researcher has uncovered twenty seven published and non-published treatises. In this dissertation, the work of the eminent Ḥadtih scholars is collated, vetted and analyzed, while this introductory analysis is about the Ḥadtih books published particularly during the period ء1901 to ء2015. This research study will be helpful in realizing the arduous efforts and valuable services rendered by the experts in the field of Ḥadtih.